2018
DOI: 10.32345/2664-4738.3-4.2018.06
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Tumor Necrotic Factor Alpha in Development of Nephropathy in Type 2 Diabetes Mellitus

Abstract: Relevance. The value of tumor necrosis factor alpha (TNFα) and the polymorphism of its gene rs1800629 for the development of type 2 diabetes mellitus (DM) has been shown in some studies but the mechanism of such an effect and role in some ethnic populations of patients is not fully understood. Objective: to find out the value of TNFα and polymorphism of its gene rs1800629 in the development of type 2 DM and its vascular complications. Materials and methods. The study involved data from 152 Ukrainia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Gupta et al, in north India on 100 DN patients showed that the carriers of −1031T/C were significantly associated with high TNF‐α levels and risk of development of DN 19 . Moreover, Ziablitsev et al study on 152 Ukrainian patients with T2D showed that the presence of the allele A rs1800629 was an important factor in DN development, and Allele A contributed to a decrease in the velocity of glomerular filtration 71 . Consistent with the above mentioned studies, our pooled analyses found a statistically significant association between the C allele vs the T allele (rs1799964) and the risk of DN.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al, in north India on 100 DN patients showed that the carriers of −1031T/C were significantly associated with high TNF‐α levels and risk of development of DN 19 . Moreover, Ziablitsev et al study on 152 Ukrainian patients with T2D showed that the presence of the allele A rs1800629 was an important factor in DN development, and Allele A contributed to a decrease in the velocity of glomerular filtration 71 . Consistent with the above mentioned studies, our pooled analyses found a statistically significant association between the C allele vs the T allele (rs1799964) and the risk of DN.…”
Section: Discussionmentioning
confidence: 99%